Education and access to fish but not economic development predict chimpanzee and mammal occurrence in West Africa. (February 2015) - Junker, Jessica; Boesch, Christophe; Mundry, Roger; Stephens, Colleen; Lormie, Menladi; Tweh, Clement; Kühl, Hjalmar S.
Graphical abstract: Highlights: We examine socio-economic correlates of wildlife existence and abundance in Liberia. We control for effects of human pressure, forest cover and cultural diversity. High chimpanzee density spatially links to high literacy and affordable fish protein. Improved rural development coincides with reduced large mammal diversity. We stress the importance of integrated socio-ecological studies to inform conservation. Abstract: We are in the midst of an unprecedented environmental crisis. Landscapes have become complex social-ecological systems in which anthropogenic activities and biophysical factors interact across multiple scales. The integration of socio-economic development processes into conservation strategies as a means of sustainable resource management requires a deep understanding of the interactions between human activities and natural processes. Attempts to combine socio-economic and biological datasets for analyses, however, have frequently been hampered by spatial, temporal and methodological incompatibilities. In this study, we investigate the effects of human well-being on their environment in Liberia, West Africa. More specifically, we tested whether regions with improved community and household wealth, better education and access to market towns and fish protein, had higher levels of large mammal species richness and densities of the flagship species of West African forests, the chimpanzee ( Pan troglodytes verus ). Controlling for human pressure, forest cover and cultural diversity, we found that high literacy rates and affordable fish protein correlated with high chimpanzee density. On the other hand, areas with better economic and infrastructure development coincided with reduced large mammal species richness compared to less developed areas. This indicates that wildlife depletion rates can only be understood by including economic and social constraints. These results are important for informing effective future conservation management strategies in Liberia and elsewhere in tropical Africa.